2013
DOI: 10.7150/ijms.6084
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Semisynthetic Molecule Icaritin Stimulates Osteogenic Differentiation and Inhibits Adipogenesis of Mesenchymal Stem Cells

Abstract: Background We previously reported that the constitutional flavonoid glycosides derived from herb Epimedium (EF, composed of seven flavonoid compounds with common nuclear stem) exerted beneficial effects on the bone, including promoting bone formation and inhibiting bone marrow fat deposition. Recent in vivo study showed that Icaritin was a common metabolite of these constitutional flavonoid glycosides, indicating that Icaritin is a bioactive compound. The present study was designed to investigate whether Icari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 29 publications
1
23
0
1
Order By: Relevance
“…Previous ex vivo studies have revealed that, in addition to having inhibitory effects on osteoclast proliferation, maturation, and differentiation, estrogens can inhibit adipocyte differentiation and function via down-regulation of the expression of adipogenesis-related genes. In a recent study, Sheng et al 18 investigated the effect of ICA on mice MSCs induced to differentiate into either osteoblasts or adipocytes. 42<44 Other osteoporosis treatments have been shown to inhibit marrow adipogenesis in vivo; for example, risedronate and peroxisome proliferator-activated receptor-F 2 antagonist (bisphenol-A-diglycidyl ether) have been shown to lower marrow adipose tissue volume in both human and animal models.…”
Section: Groupsmentioning
confidence: 99%
“…Previous ex vivo studies have revealed that, in addition to having inhibitory effects on osteoclast proliferation, maturation, and differentiation, estrogens can inhibit adipocyte differentiation and function via down-regulation of the expression of adipogenesis-related genes. In a recent study, Sheng et al 18 investigated the effect of ICA on mice MSCs induced to differentiate into either osteoblasts or adipocytes. 42<44 Other osteoporosis treatments have been shown to inhibit marrow adipogenesis in vivo; for example, risedronate and peroxisome proliferator-activated receptor-F 2 antagonist (bisphenol-A-diglycidyl ether) have been shown to lower marrow adipose tissue volume in both human and animal models.…”
Section: Groupsmentioning
confidence: 99%
“…Icariin (ICA, C 33 H 40 O 15 ; molecular weight: 676.67) is the major flavonoid glycoside extracted from Epimedium and is considered the main active constituent. ICA may exert favorable osseointegration effects by enhancing the differentiation of MSCs into osteoblasts while inhibiting the adipogenesis of bone marrow cells [17] and can treat osteoporosis by increasing bone mineral content [18]. Recently, ICA has been widely applied for bone tissue engineering due to its safe, nontoxic, and osteoinductive properties as well as its low cost [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Icaritin, a prenylflavonoid derivative from the Chinese tonic herb Epimedium, has been shown to have many pharmacological and biological activities, such as antioxidant activity [1] , enhancement of the osteoblastic differentiation of mesenchymal stem cells [2][3][4] , inhibition of human prostate carcinoma growth [5,6] and neuroprotective effects [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%